Phase 2 Trial of Stereotactic Body Radiation Therapy with Dose Escalation Using Simultaneous Integrated Boost for Spinal Metastases - Takamasa Mitsuyoshi, MD, PhD; Peter J. K. Tokuda, MD; Yumi Kokubo, MD; Takahiro Iwai, MD; Hiroyuki Inoo, MD; Ryo Ashida, MD, PhD; Ryosuke Nasada, MS; Mikiko Yamashita, PhD; Hiroaki Tanabe, MS; Shigeki Arizono, MD, PhD; Toshiyuki Imagumbai, MD; Masaki Kokubo, MD, PhD (Advances in Radiation Oncology)
Purpose: Stereotactic body radiation therapy (SBRT) is an effective treatment approach for spinal metastases. However, local recurrence may occur. This prospective phase 2 trial evaluated whether SBRT with dose escalation in the gross tumor volume through simultaneous integrated boost (SIB–SBRT) can improve local control (LC) without increasing adverse events (AEs). Methods and Materials: Eligible patients aged ≥ 20 years with spinal metastases and a life expectancy of > 1 year received SIB–SBRT in 5 fractions over 1 week. The prescribed dose was 30 Gy to the planning target volume for evaluation and an escalated dose of 40 to 45 Gy to the gross tumor volume through SIB. Neurologic examinations and magnetic resonance imaging were performed at 3-, 6-, and 12-month follow-up and every 6 months thereafter. The primary endpoint was the 1-year LC rate. The secondary endpoints included overall survival and AEs, such as vertebral compression fractures (VCFs). Results: A total of 25 patients with 28 vertebral segments from September 2020 to March 2023 were enrolled in this study. The median follow-up was 26.2 months, and 24 segments in 21 patients were followed up for >1 year. The 1- and 2-year LC rates were 100.0% and 95.0%, respectively. Local recurrence developed in only 1 patient at 18 months. The 1- and 2-year overall survival rates were 92.0% and 72.8%, respectively. Six patients developed VCFs (3 cases each of grades 1 and 2), with 1- and 2-year cumulative incidence rates of 3.6% and 15.6%, respectively. No radiation myelopathy or other grade ≥ 2 AEs occurred, except for 1 case of grade 2 pain. Conclusions: Dose-escalated SIB–SBRT for spinal metastases demonstrates excellent LC with acceptable toxicity, supporting the need for a larger comparative trial.